2014
DOI: 10.3389/fmed.2014.00004
|View full text |Cite
|
Sign up to set email alerts
|

Knowing What’s Out There: Awareness of Non-Alcoholic Fatty Liver Disease

Abstract: Background: Non-alcoholic fatty liver disease (NAFLD) is the most common hepatic disorder, which poses a significant health burden in the western countries. As the epidemic of obesity slides health downward, the incidence of NAFLD is evidently increasing.Aim: We aimed to ascertain the awareness of NAFLD and its risk factors in the general population, which may be helpful in designing educational tools to promote prevention, early detection, and treatment of this disorder.Methods: A survey of 5000 non-instituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
41
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(47 citation statements)
references
References 19 publications
(24 reference statements)
3
41
2
1
Order By: Relevance
“…Also of note, an additional one third of NAFLD patients were under the care of a GI provider for other conditions (eg, acid reflux and diarrhoea), but they did not receive care related to NAFLD. Taken together, this pattern of care reflects low disease awareness among patients and providers, even in the face of multiple metabolic risk factors . These care patterns also reflect perceptions regarding the clinical significance and treatment options for NAFLD held by many providers .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Also of note, an additional one third of NAFLD patients were under the care of a GI provider for other conditions (eg, acid reflux and diarrhoea), but they did not receive care related to NAFLD. Taken together, this pattern of care reflects low disease awareness among patients and providers, even in the face of multiple metabolic risk factors . These care patterns also reflect perceptions regarding the clinical significance and treatment options for NAFLD held by many providers .…”
Section: Discussionmentioning
confidence: 91%
“…Taken together, this pattern of care reflects low disease awareness among patients and providers, even in the face of multiple metabolic risk factors. 21,22 These care patterns also reflect perceptions regarding the clinical significance and treatment options for NAFLD held by many providers. 23 This low rate of referral to GI/Hepatology is in line with data from prior studies where 71% of providers reported that they did not refer patients with suspected NAFLD to GI/Hepatology.…”
Section: Discussionmentioning
confidence: 94%
“…But, since NASH can spontaneously regress, this question will be an important one to ask when studying the natural history of NAFLD/NASH. Therefore, to increase awareness, we recommend that focus be continued on educating not only the public but also the healthcare practitioners who are most likely to encounter NAFLD patients first .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies (5, 6) have shown that NAFLD is not regarded as a clinically important diagnosis by a significant proportion of providers who underestimate disease prevalence among their patients and do not identify those factors associated with more serious or advanced disease (7). The latter determines a non-focused management and limited referral of patients to hepatology clinics and, eventually, to lack of recognition of advanced liver disease.…”
mentioning
confidence: 99%